Transition from SAK ETAP to SAK EMKM at the Association of Blood Management Units, Blood Banks and Plasma Banks of Indonesia: an analysis of challenges and opportunities - Yudi Jemiran; Richard Andrew (CONTABILITA : Journal of Accounting and Finance, 2026)
This study aims to examine the various challenges and opportunities faced by the Association Blood Management Units, Blood Banks and Plasma Banks of Indonesia in the process of transition from Financial Accounting Standards of entities without public accountability (SAK ETAP) to Financial Accounting Standards of private entities (SAK EMKM). The approach used is qualitative with phenomenological design, involving internal auditors, external auditors, and accounting staff as the main informants. Data collection was conducted through semi-structured interviews and analyzed using thematic analysis techniques. The results showed that the implementation of SAK EMKM raises various obstacles, especially related to the complexity of the standard, the need for adjustment of internal systems, as well as the limitations of Human Resource competence. On the other hand, the implementation of SAK EMKM provides benefits in the form of improving the quality, consistency, and credibility of financial statements, as well as encouraging the professionalism of accounting personnel. With the right adaptation strategy, this transition has the potential to provide long-term added value in strengthening the governance and reliability of association organization financial reporting.